A comparison of intravenous lignocaine, intraperitoneal lignocaine, a combination of both on bowel recovery and pain relief in patients undergoing laparoscopic cholecystectomy - Puram, Unnikrishnan E.; Raghavan, Rajesh M.; Appunny, Anoop M. (International Journal of Research in Medical Sciences, 2017)
Background:Laparoscopic cholecystectomy (LC) is being increasingly performed as a day care surgery. Pain and lack of early bowel movements are common reasons preventing discharge on the same day. Methods: Study was conducted in a Government tertiary care institute in Kerala, South India. The effect of Intraperitoneal (IP), Intravenous (IV) and a combination of both on postoperative pain relief and bowel recovery was studied in 75 patients who were randomized in to 3 equal groups undergoing elective laparoscopic cholecystectomy. Group 1 IP lignocaine, Group 2 IV lignocaine and Group 3 combination of IP and IV lignocaine. Results: The time of bowel recovery and the pain scales at different time was compared using ANOVA test. Intergroup comparison of bowel recovery and pain scale was done using Bonferroni test. Pain score shows a statistically significant difference between Group 1 and Group 2 with a p value <0.001 and a statistically significant difference between Group1 and Group3 with a p value 0.126, but no statistical significance between Group 2 & Group3. The return of bowel activity was noted with perception of bowel movements and time for passage of flatus compared among the group, there was a statistically significant difference between the three groups. Group 2 was found to be significantly better than the Group1 and Group3. Conclusions: Intravenous lignocaine is superior in bringing out early return of bowel activity when compared to all groups and Intravenous lignocaine is superior compared to intraperitoneal lignocaine in pain relief.